Dairy consumption patterns in southern Nigeria - Jabbar, M.A.; Domenico, C.M. di (International Livestock Centre for Africa, 1992)
A survey was conducted of 982 indigene households and 203 Hausa/Fulani households in southern Nigeria between October 1988 and March 1989. Results show that 70 percent of the indigenes and 98 percent of the Hausa/Fulani consumed some dairy products. Prevalence and regularity of consumption of local products among the indigenes was high around the points of production but low elsewhere, while the regularity of consumption for imported products was high among both indigenes and the Hausa/Fulani. The type and quantity of products consumed and expenditure on dairy products deffered markedly among ethnic groups, urban and rural populations and between the south-west and the south-east. Per caput income of indigenous households that consume dairy products did not differ significantly in any of the locations from that of indigenous households that did not consume dairy products. Among the consumers, income elasticity demand was higher for rural households in the south-west and for urban households in the south-east and was higher for urban Hausa than rural Fulani, who are producers of dairy products.